2016
DOI: 10.1177/0267659116634829
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulsatile cardiopulmonary bypass on the need for haemofiltration in patients with renal dysfunction undergoing cardiac surgery

Abstract: Within the limitations imposed by retrospective analyses, our study demonstrates that pulsatile CPB may confer a reno-protective effect in higher-risk patients with pre-existing mild renal dysfunction undergoing cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Its impact on clinical outcomes has been extensively studied in a variety of settings; however, the data on renal outcomes are conflicting because of the lack of uniformity in pulsatility delivery . A retrospective analysis showed pulsatile CPB conferred a renoprotective effect in higher risk patients undergoing cardiac surgery . However, the contemporary use of implantable continuous‐flow left ventricular assist devices challenges this concept .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its impact on clinical outcomes has been extensively studied in a variety of settings; however, the data on renal outcomes are conflicting because of the lack of uniformity in pulsatility delivery . A retrospective analysis showed pulsatile CPB conferred a renoprotective effect in higher risk patients undergoing cardiac surgery . However, the contemporary use of implantable continuous‐flow left ventricular assist devices challenges this concept .…”
Section: Resultsmentioning
confidence: 99%
“…159,[183][184][185] A retrospective analysis showed pulsatile CPB conferred a renoprotective effect in higher risk patients undergoing cardiac surgery. 186 However, the contemporary use of implantable continuous-flow left ventricular assist devices challenges this concept. 187 The improvement in the hemodynamic environment provided by continuous-flow left ventricular assist devices leads to better renal function in heart failure patients, implying that the theoretical importance of pulsatility is superseded by increased cardiac output.…”
Section: Nonpharmacological Strategiesmentioning
confidence: 99%
“…Other possibilities include the potential for confounding owing to the authors' study design and limitations (discussed later) and the possibility of publication bias and duplication affecting the meta-analyses. Since these meta-analyses, 1 small observation study has shown no significant difference in outcome, 12 and another found an improvement in creatinine clearance. 19…”
Section: Findings In Contextmentioning
confidence: 99%
“…This decision was based on the favorable risk-benefit profile described earlier (improved microvascular flow, improved renal perfusion, and reduced renal injury) and seen in studies to date. 8,12 There were no other changes in practice or surgical population between these 2 periods that the authors were aware of. The authors therefore subsequently performed a before-and-after study to compare outcomes between nonpulsatile and pulsatile CPB.…”
mentioning
confidence: 99%
See 1 more Smart Citation